Keakraban Produk dan Minat Beli Frozen Food: Peran Pengetahuan Produk, Kemasan, dan Lingkungan Sosial - Imam Santoso; Siti Asmaul Mustaniroh; Dodyk Pranowo (Jurnal Ilmu Keluarga dan Konsumen, 2018)
The dynamics condition of society is increasing due to the lifestyle change including shifthing patterns of food consumption from fresh raw food to frozen food products in some of consumers. Nowdays, frozen food products become an alternative options of households to fulfill food needed. Frozen food products is vary so will be influence that the demand of consumers’s ability in choosing the best processed food products. This research aimed to analyze the relationship between the product knowledge, packaging, and social environment on familiarity of products and relationship between familiarity of products and purchasing intention among consumers of frozen food. This research was conducted in the Ketawanggede and Dinoyo Village, Lowokwaru Subdistrict, Malang City. Data collection used judgement sampling with the questionnaire as instrument of data collecting. The total of respondents were 111 customers who have cunsomed frozen food at least twice a month in the last-three month when data collecting was conducted. The data analysis used the Generalized Structured Component Analysis (GSCA). The result showed that product knowledge has no significant effect on product familiarity. Packaging and social environment proven have significant effect on product familiarity. Product familiarity also have significant effect on purchasing intention of frozen food.